Multimedia : making it work - Vaughan, Tay. (McGraw-Hill Education, 2014)
"This thoroughly revised and updated full-color text covers the most current multimedia tools, techniques, and technologies, including Web and mobile content design and deliveryMultimedia: Making It Work, Eighth Edition teaches fundamental multimedia concepts and shows you the process of managing multimedia production. Beginning with the essential multimedia building blocks of text, images, sound, animation, and video, the book educates you on the business of making multimedia. Project planning, costs, design, production, talent acquisition, testing, and delivery are also covered. Discussions of the most up-to-date technologies run throughout the chapters, with coverage of Multimedia Messaging Service (MMS), the architecture for multimedia content delivery used in mobile devices. Lab projects have been updated with applications of multimedia on the Web, such as shooting videos on a cell phone and uploading the results to websites. Both Windows and Mac environments are covered. Starting with this edition, software tools will be drawn from Open Source and shareware. Each chapter of the text focuses on highlighted learning objectives and includes chapter summaries, key term lists, end-of-chapter quizzes, and lab projects. Multimedia: Making It Work, Eighth Edition features: New coverage of Multimedia Messaging Service (MMS), the architecture for multimedia content delivery to mobile devices Updated lab projects that feature multimedia Web applications A focus on open source software tools Free Online Learning Center with two user interfaces: student interface includes objectives and links to chapter quizzes; instructor interface hosts instructors guide, course syllabus, end-of-chapter question solutions, PowerPoint slides, and a link to an EZ Test test bank. CD-ROM with all the chapter review questions from the book in a practice test application and trial versions of different multimedia software All-inclusive coverage: What is Multimedia; Text; Images; Sound; Animation; Video; Making Multimedia; Multimedia Skills; Planning and Costing; Design and Production; Content and Talent; The Internet and Multimedia; Designing for the Web; Delivering"--